2001
DOI: 10.1111/j.1439-0434.2001.tb03867.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role for Ethylene in Susceptibility of Tomato to Verticillium Wilt

Abstract: Ethylene has been observed to both inhibit and promote the symptoms of Verticillium wilt (caused by Verticillium dahliae) in tomato. To test the hypothesis that ethylene has dierent eects at dierent stages in the infection process, ethylene levels were manipulated in V. dahliaeinfected tomato plants by the application of an ethylene synthesis inhibitor aminoethoxyvinylglycine (AVG) and/or ethylene's biosynthetic precursor 1-aminocyclopropane-1-carboxylate (ACC) and the eects on disease severity were examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…It is possible that the reduction in the amount of stress ethylene by ACC deaminase can lead to a reduction in the pathogen‐induced disease symptoms (Robison et al. 2001a,b).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the reduction in the amount of stress ethylene by ACC deaminase can lead to a reduction in the pathogen‐induced disease symptoms (Robison et al. 2001a,b).…”
Section: Discussionmentioning
confidence: 99%
“…This ET dichotomy has also been observed in tomato plants treated with the ET precursor, 1-aminocyclo-propane-1-carboxylate (ACC), at the time of inoculation to produce an initial transient burst of ET, and then blocked the ET production by adding the ethylene biosynthesis inhibitor aminoethoxyvinylglycine (AVG). By this consecutive treatment with ACC and AVG, symptom severity caused by V. ahlia is reduced further than each treatment alone [ 17 ]. Besides its involvement in resistance, ET controls symptom development in tomato [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene has been involved in both resistance and susceptibility to Verticillium [ 17 ]. Robison et al [ 17 ] showed that post-infection ethylene enhances Verticillium wilt development in tomato, whereas its presence at the time of infection inhibits disease development. In pepper, expression of a basic PR-1 is positively regulated by ET [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The process of plant response to pathogenic bacteria is regulated by multiple signals, in which plant hormones play a key role (Katagiri and Tsuda 2010). Previous studies suggested that ET had a multiple effect on the interaction between plants and Verticillium wilt, with several genes activated by ET in response to Verticillium wilt, including ethylene responsive factor (ERF6), ERF1 and GbERF1-like (Robison et al 2001;Yang et al 2015;Guo et al 2016). These transcription factors regulated the expression of downstream resistance proteins and increased the plant disease resistance.…”
Section: Discussionmentioning
confidence: 99%